The Advent of Sexual Ethics in Rabbi Abraham Ben David of Posquières's Ba'alei Ha-Nefesh: הולדתה של האתיקה המינית של חדר המיטות בספר בעלי הנפש לראב"ד - Moryossef, Itai (AJS review, 2025)
Rabbi Abraham ben David (Rabad) was a Talmud commentator, a rosh yeshiva in the city of Posquières in the Provence region of France, and was one of the first kabbalists. In the last third of the twelfth century, Rabad wrote Baʿalei ha- nefesh, a mainly halakhic treatise (six chapters on the laws of niddah). Rabad added an introduction and a seventh chapter at the end on moral issues. Baʿalei ha-nefesh is a unique book in several respects, most significant of which is Rabad’s formulation of a sexual ethics alongside the halakhic discussion. There has not yet been an overall assessment of Rabad’s purpose in his chapter on holiness (Shaʿar ha-kedushah): the creation of a sexual ethics. While before Rabad, Jewish authors addressed halakhic issues related to sexuality, none had dedicated a work to sexual ethics or sexual philosophy. Rabad founded a field that did not exist before him, and approached it in an innovative way. This article will explain this innovation through a literary and philosophical study and analysis of Shaʿar ha-kedushah.